Sexually transmitted infections and associated factors among Wollo University students, Northeast Ethiopia - Hilina Ayalew; Gedefaw Abeje; Elsabeth Addisu; Natnael Kebede; Ayalew Hassen Mohammed (HIV & AIDS Review. International Journal of HIV-Related Problems)
Introduction Sexually transmitted infections (STIs) represent a large burden worldwide, with an annual incidence of about 333 million cases. In Ethiopia, studies on STIs among youths are very few. Investigating STIs in general and particularly among youths, is an important input to designing policies and strategies aimed at preventing and controlling infections. Therefore, the aim of this study was to determine the prevalence and associated factors of STIs among Wollo University students, in Northeast Ethiopia.